E-Book Based on Problem Based Learning Model in Science Lessons on Me and My Needs Class IV Elementary School - Ni Putu Desy Arnila Dewi; Ida Bagus Gede Surya Abadi; Anak Agung Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2025)
The lack of active student engagement in Science and Social Studies (IPAS) learning becomes the focus of this study. This research aims to develop and evaluate the effectiveness of an interactive e-book based on the Problem Based Learning (PBL) model in enhancing student engagement and learning outcomes. The study employs a development research design using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of 30 grade IV students. Data collected included qualitative and quantitative data, obtained through observation, interviews, questionnaires, and multiple-choice tests. Data analysis was conducted using qualitative descriptive methods to assess media quality and user responses, as well as quantitative descriptive methods to evaluate the e-book’s effectiveness on student learning outcomes. The results indicate that the developed e-book has very high validity according to expert assessments, is considered practical by teachers and students, and effectively improves learning outcomes. The implications of this study suggest that the PBL-based interactive e-book can serve as an innovative, student-centered learning media alternative, fostering 21st-century skills such as critical thinking, collaboration, and problem-solving abilities. This research provides a foundation for developing contextual, interactive digital learning media that are relevant to the needs of modern learners.